HYPERBOLE IN ALBUM “AMBITIONS” BY ONE OK ROCK - A.A Putu Gede Raditya Pratama; I Wayan Juniartha (CV. Multi Kreasi Media, 2023)
The purpose of this research is to identify and analyze the meaning of hyperbole used in song lyrics in the Ambitions album from ONE OK ROCK. Hyperbole is used to exaggerate the actual reality contained in the lyrics of the song. The data in this research are presented descriptively. To collect data, this research used observation and note-taking techniques. The data is taken from song lyrics in Ambitions album by One Ok Rock. In analyzing the data, the writer uses the figurative language theory proposed by Abrams (1999), and the meaning theory proposed by Leech (1981). The results showed that there were ten hyperboles found in the song lyrics. The meaning found based on the lyrics with hyperbole consists of two kinds, namely connotative and affective.